Faktor Pengetahuan dan Perilaku Petani Penyemprot yang Berhubungan dengan Kadar Serum Cholinesterase di Kabupaten Brebes - Devi Ayu Susilowati; Suhartono Suhartono; Bagoes Widjanarko (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2018)
Background: Spray farmers are is one of the population at risk for pesticide poisoning. To determine the presence of pesticide exposure and risk assessment of pesticide poisoning is by measuring serum ChE levels. Based on the data results of ChE examination by Brebes District Health Ofﬁce found 5.5% mild poisoning in Dukuhlo Village. This study aims to analyze the relationship between knowledge, attitude and behavior of the use of pesticides with serum cholinestearse levels in spraying farmers.Method: This research use cross sectional design. Involved 88 farmer sprayers in Dukuhlo Village. The research variables were age, nutritional status, knowledge, attitude, completeness of PPE, smoking when spraying, spraying on wind direction, cleaning sweat by hand or cloth, reentering agriculture area, spraying time, frekuesni spraying, pesticide storage method, and Last time to spray. Data were analyzed by multivariate analysis.Results: Factors shown to be associated with serum ChE levels were knowledge of pesticides (p= 0.005; OR: 12,369; 95% CI = 2,1-71,5) and smoking when spraying (p = 0.005; OR: 9,641;95% CI = 2.0-46.1). Factors not shown to be associated with se rum ChE levels are age, nutritional status, attitude, completeness of APD application, spraying on the wind direction, sweating with hands or cloth, reentering agriculture, spraying, fracturing spraying, Pesticides, and last time to spray.Conclusion: Factors associated with serum ChE levels are knowledge of pesticides and smoking when spraying. Health counseling is needed to increase knowledge about pesticides and the dangers of smoking while spraying.